The Williamsburg Charter: A Response to History, Distant and Recent - Buchanan, John H. (Journal of law and religion, 1990)
Those who drafted the Williamsburg Charter tell us that they did so in celebration of the 200th anniversary of the Bill of Rights. But it also seems to me no mere coincidence that the Charter's reaffirmation of religious liberty and re-examination of the role of religion in America's public life comes at the end of a decade that saw a mixing of politics and religion that troubled many of us deeply.As the Charter itself emphasizes, religious people and religious ideas have long played a role in our public life. Those people and ideas are welcome elements of our ongoing national debate about what kind of a society we want to be. But during the Eighties, the debate about the role of religion in our public life often became uncivil and divisive and religious extremism often held sway over the voices of tolerance and moderation.